Co-Therapy of Pegylated G-CSF and Ghrelin for Enhancing Survival After Exposure to Lethal Radiation - Kiang, Juliann G.; Zhai, Min; Lin, Bin; Smith, Joan T.; Anderson, Marsha N.; Jiang, Suping (Frontiers in Pharmacology, 2021)
Exposure to ionizing radiation (radiation injury, RI) in nuclear-related episode is evident to be life-threatening. RI occurs at levels of organs, tissues, cytosols, or nucleus. Their mechanisms are still not fully understood. FDA approves pegylated granulocyte colony-stimulating factor (Neulasta, Peg-G-CSF) for acute hematopoietic syndrome and has been shown to save lives after lethal RI. We aimed to test whether Ghrelin enhanced Peg-G-CSF’s efficacy to save more lives after lethal RI. B6D2F1/J female mice were used for the study. They received 9.5 Gy (LD50/30 at 0.4 Gy/min) emitted from the 60Co-γ-photon radiation facility. Peg-G-CSF was injected subcutaneously at 1 mg/kg once on days 1, 8, and 15 after irradiation. Ghrelin contains 28 amino acid and is a hunger peptide that has been shown to stimulate food intake, promote intestinal epithelial cell proliferation, elevates immunity, inhibits brain hemorrhage, and increases stress-coping. Ghrelin was injected subcutaneously at 113 µg/kg once on days 1, 2, and 3 after irradiation. Survival, body weight, water consumption, hematology, spleen weight, splenocytes, bone marrow cells, and histology of bone marrow and ileum were performed. We observed that radiation resulted in 30-day survival by 30%. RI decreased their body weights and water consumption volumes. On the 30th day post-RI, platelets and WBCs such as basophils, eosinophils, monocytes, , lymphocytes, neutrophils and leucocytes were still significantly decreased in surviving mice. Likewise, their RBC, hemoglobin, hematocrit, and splenocytes remained low; splenomegaly was found in these mice. Bone marrow in surviving RI animals maintained low cellularity with high counts of fat cells and low counts of megakaryocytes. Meanwhile, ileum histology displayed injury. However, mice co-treated with both drugs 24 hr after RI resulted in 30-day survival by 45% above the vehicle group. Additionally, the body-weight loss was mitigated, the acute radiation syndrome was reduced. This co-therapy significantly increased neutrophils, eosinophils, leucocytes, and platelets in circulation, inhibited splenomegaly, and increased bone marrow cells. Histopathological analysis showed significant improvement on bone marrow cellularity and ileum morphology. In conclusion, the results provide a proof of concept and suggest that the co-therapy of Peg-G-CSF and Ghrelin is efficacious to ameliorate RI.